Stumbayan: A feasibility study on a place for studying, staying for leisure, and resting in Intramuros, Manila - Canales, Roel P., Cebreros, Hazel B., Cloma, Carisa D., Dig, Mary Christine Erica J., Lapuz, Steffani Gwen D. 4 0 16; 5
EXECUTIVE SUMMARY Name of the Company Stumbayan is the name of the business, wherein it is a portmanteau that combines two words; hence, the original words' sounds and meanings are combined to produce a new word. The words Study and Tambayan combined, we formed Stumbayan. Tambayan is a Filipino word that means a place for hanging out. In the same meaning as Stumbayan, we aim to provide people with a place to study, hang out, and even rest. A place for educational and recreational purposes where the business aim to provide a safe space for students to stay during their free time or work on their time productively. Company Logo Each feature of the business logo was well-planned. As illustrated, the brick background in the logo represents the local culture of the location of the business, which is Intramuros, Manila. The inspiration was made since Intramuros is also known as the 'Walled City.' From then on, it also has a section in the logo that a woman is reading while sitting in a bean bag which is one of the amenities of the business. This logo perfectly portrays the business's name, Stumbayan, a safe space where people can study, hang out, and even rest while in comfortable seating. Location of the Enterprise This study will investigate the feasibility of Stumbayan near the Universities around Intramuros, such as Pamatasan ng Lungsod ng Maynila, Mapua University, Lyceum of the Philippines University, and Colegio de San Juan de Letran. The Stumbayan will be placed at Plaza San Luis Complex in General Luna Street Corner Real Street. Brgy. 658, Zone 70, District 5, Intramuros, Manila. The proponents find the store space rental in this location suited for the business as it is only an estimated 5-8 minutes walk from the universities of its target customers, college students. For the business to expand, this Stumbayan should be feasible to prove its profitability and worthiness to the market. Description of the Business The study will dig deeper into serving students by establishing a safe space for studying, staying for leisure, and resting in Intramuros, Manila. This place was created primarily to satisfy the needs and wants of students who need a cozy and comfortable place to study, work on school projects, engage with others, take a nap, stay during long breaks, and even eat. In short, this place is both for the education and recreation of solo or group students, as Stumbayan have different amenities to accommodate them. Moreover, Stumbayan provides free Wi-Fi and power outlets, unlimited water, and 1-2 cups of brewed coffee per person. Furthermore, for students' convenience, the store offers products and other services inside, particularly a printing press and renting board games, snacks, and canned drinks. Last, if they need a restroom, the store has a common bathroom. Long-run Objectives This study aims to determine the feasibility of establishing a place for studying, leisure, and resting in General Luna St. Intramuros, Manila, for students' educational and recreational purposes. The company aims to provide students with a cozy, air- conditioned place with comfortable seatings that accommodate individuals and groups. Also, it aims to meet various needs. It wants students in different universities in Intramuros, Manila, regarding a study/leisure lounge by offering different amenities, complementary and purchasable products, and services at an affordable price and convenient location. If the business is established, it will be the first official study/leisure lounge in Intramuros, Manila, and it aims to expand its store, amenities, products, and other services for the succeeding years for students' convenience and satisfaction. Highlights of Major Assumptions The Company assumes a market for a study/leisure lounge in Intramuros, Manila, considering that universities are located around the area. The Company assumes that students are seeking a comfortable place to stay and take a nap or hang out with peers, or for those students who have a long break in between and are looking for a place to relax or study, or spaces in universities can be insufficient to accommodate all students, distracting for certain activities or restricted enough for students to collaborate, and other reasons. Therefore, it is assumed that there is a demand for a place that offers spaces for educational and recreational purposes, along with its products and other services that meet students' various needs and wants at an affordable price and convenient location. Moreover, the researchers posit a demand for solo and productive space to read, study or do school works that need focus. As well as tables and chairs for meetings and gatherings of students in making school projects like thesis, researchers included amenities that can accompany students individually, in pairs, or groups. Last, the Company assumes there will be a demand for printing as not all students have printers in their homes, affordable snacks for students to consume during their stay, and renting board games to unwind or hang out with friends. Summary of Findings In general, Stumbayan is feasible after conducting all of the necessary research in different aspects and arriving at positive findings like the following: The company's amenities are different, and its products and services are high quality but cheaper than the other cafés in the location, which are businesses that could also be a place for staying people. In the case of other study/leisure lounges, Stumbayan is nearer and in a more convenient location for students studying in Intramuros. Also, the variety of its amenities, which can accompany solo, pair, and group, gives more options in its target market. The computed market share and maximum safe estimate of annual capacity of Stumbayan's amenities, products, and other services after opening the company in Intramuros, Manila, are as follows: 7,508 Cubicles, 4,205 Bean Bags and 22,074 Bean bags with Board games, 22,524 Floor-style Tables, 13,139 Tables, and Chairs, 33,788 in Printing Press, 3,916 Nachos, and 3,446 Assorted Sweets (Brownies) in the preceding year is assumed considering the capacity of the store and the projected annual demand from college students studying in universities in Intramuros, Manila.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2